Inhibition of Thromboplastin Activity in Plasma by Aluminosilicate Treatment - Chenkin, Theodore; Moses, Doris; Perel, James M.; Weiner, Murray (Thrombosis and Haemostasis, 1972)
Permutit, a synthetic aluminosilicate is an ion exchange agent which, on mixing with plasma produces a prolongation of the clotting time, change in pH, and removal of some gamma globulin and alpha and beta lipoprotein. Heat-inactivation of the ion-exchange property of Permutit also eliminates these effects on plasma. Some of these changes also occur on mixing Permutit with extrinsic thromboplastins.The evidence presented suggests that the prolonged clotting time is not due to the removal of one or more clotting factors from plasma treated with Permutit.It is concluded that the prolongation of clotting time produced by Permutit treatment of plasma is due to the formation or release of a potent thromboplastin inhibitor.